PSI-38 Evaluation of increasing oat groats in nursery pig diets. (5th December 2019) - Chance, Jenna; Lerner, Annie; DeRouchey, Joel; Woodworth, Jason; Tokach, Mike; Goodband, Robert
Abstract: Two experiments were conducted to test the effect of added dietary oat groats on nursery pig performance (Exp. 1) and diet palatability (Exp. 2). In Exp. 1, a total of 225 pigs (initially 6.3 kg) were used in a 14-d study. Pigs were fed a starter diet for 7 d prior to the start of the experiment. Pens were assigned to 1 of 5 dietary treatments in a RCBD by BW with 4 or 5 pigs/pen and 10 pens/treatment. Dietary treatments consisted of 0, 7.5, 15, 22.5, or 30% oat groats added as a replacement for corn. Treatments were fed for 14 d with pig weights and feed disappearance collected weekly. Data were analyzed using PROC GLIMMIX. For the experimental period, increasing added oat groats resulted in no evidence for differences (P > 0.05) in ADG, ADFI, G:F, or d 14 BW. In Exp. 2, a 7-d preference study was conducted to evaluate the response when given the choice between 0% oat groats to either 7.5% groats or 30% groats. A total of 48 pigs were used with 4 pigs/pen and 6 replications/comparison. Pigs were weighed on d 0 and 7, and feeders weighed and position rotated within the pen daily to determine ADFI of each diet offered. When given the choice, there was no evidence for difference (P > 0.05) in ADFI or percentage of diet consumed between the 0% and 7.5% oat groat diets. When given the choice between the 0% or 30% groat diets, pigs had increased (P = 0.001) ADFI (0.05 vs. 0.29 kg, respectively; SEM=0.020) and feed consumed (16.3 vs. 83.7%, respectively; SEM=3.61) with the 30% oat groat treatment. In conclusion, increasing dietary oat groats did not improve performance; however, when given the choice, pigs preferred the 30% oat groat diet compared to diets without oat groats.